Mapdisto: fast and efficient computation of genetic linkage maps - Lorieux, Mathias (Springer, 2012)
MapDisto is a program for mapping genetic markers in experimental segregating populations like backcross, F2, doubled haploids, single-seed descent and highly recombinant lines. One of its specificities is to propose recombination fraction estimates in case of segregation distortion. MapDisto has many features such as drawing genetic maps, computing allelic disequilibrium, finding linkage groups, automatic ordering of loci, simple QTL analysis and exporting data and maps for other mapping software. MapDisto needs Microsoft® Excel to run. Supported versions are Excel 2003 to 2010 for Windows; Excel 2004 and 2011 for Mac OS X.